Segregation by District Boundary Line: The Fragmentation of Memphis Area Schools. (November 2017) - Frankenberg, Erica; Siegel-Hawley, Genevieve; Diem, Sarah
Boundary lines have long served as a mechanism to divide people, determining the quality of available resources, and ultimately, educational opportunity. In recent years, new school district boundaries have proliferated as local communities attempt to secede from larger school districts. In this study of Memphis-Shelby County, Tennessee, we extend prior research on school district fragmentation and consolidation by examining the largest American school district merger—and swift, subsequent suburban secessions—in recent decades. In Memphis, policy and political actors fostered decentralization and competition through the expansion of choices among new school districts defined by highly salient racial boundaries. These actions exacerbated segregation between districts with students' racial and economic school-level exposure differing substantially across the new district lines. State and local actions that fostered the fragmentation of the consolidated district reduced possibilities for further integration and equity, with significant implications for students, families, and the larger community.